HC-HA/PTX3 Purified From Amniotic Membrane as Novel Regenerative Matrix: Insight Into Relationship Between Inflammation and Regeneration - Tseng, Scheffer C. G. (Invest Ophthalmol Vis Sci, 2016)
PURPOSE: Human limbal palisade of Vogt is an ideal model for studying and practicing regenerative medicine due to their accessibility. Nonresolving inflammation is a common manifestation of limbal stem cell deficiency, which is the major cause of corneal blindness, and presents as a threat to the success of transplanted limbal epithelial stem cells. Clinical studies have shown that the efficacy of transplantation of limbal epithelial stem cells can be augmented by transplantation of cryopreserved human amniotic membrane (AM), which exerts anti-inflammatory, antiscarring, and antiangiogenic action to promote wound healing. METHODS: Review of published data to determine the molecular action mechanism explaining how AM exerts the aforementioned therapeutic actions. RESULTS: From the water-soluble extract of cryopreserved AM, we have biochemically purified one novel matrix component termed heavy chain (HC)-hyaluronan (HA)/pentraxin 3 (PTX3) as the key relevant tissue characteristic responsible for the aforementioned AM's efficacy. Heavy chain–HA is a complex formed by a covalent linkage between HA and HC1 of inter-α-trypsin inhibitor (IαI) by tumor necrosis factor-stimulated gene-6 (TSG-6). This complex may then be tightly associated with PTX3 to form HC-HA/PTX3 complex. Besides exerting an anti-inflammatory, antiscarring, and antiangiogenic effects, HC-HA/PTX3 complex also uniquely maintains limbal niche cells to support the quiescence of limbal epithelial stem cells. CONCLUSIONS: We envision that HC-HA/PTX3 purified from AM can be used as a unique substrate to refine ex vivo expansion of limbal epithelial stem cells by maintaining stem cell quiescence, self-renewal and fate decision. Furthermore, it can also be deployed as a platform to launch new therapeutics in regenerative medicine by mitigating nonresolving inflammation and reinforcing the well-being of stem cell niche.